Anatomy and human movement : structure and function - Palastanga, Nigel; Soames, Roger (Physiotherapy essentials, 2012)
"Over the past 22 years, Anatomy and Human Movement has grown into a classic textbook, helping students to understand and remember the mechanisms which allow movement to take place. Now in its sixth edition, the approach remains the same - each section of the body is presented systematically where readers are introduced to the bones, and thein guided through the muscles, joints, nervous system and blood supply. Anatomy of teh musculoskeletal system is brought ot life thorugh simple full colour artwork following a colour key for clarity and accuracy"--Back cover.